Computational inverse techniques in nondestructive evaluation - Liu, G. R. (CRC Press, 2003)
Although many books on inverse problems already exist, they can be quite mathematical in nature and pay little attention to practical applications. This book forms a bridge between the theoretical foundations and practical applications of nondestructive evaluation methods. With unique emphasis on inverse problems in solid mechanics, it describes in detail the principles, computational methods and algorithms, and practical techniques of inverse analyses using elastic waves and dynamics responses in solids and structures. Applications of advanced computational inverse techniques to electronic sy.